Self Identity and Morality - Ludwig, David J. (Journal of psychology and theology, 1976)
A close look is given to the motivational basis for moral behavior. One aspect of morality is concern for the needs and wishes of others. The motivation for such consideration is seen as related to one's self-identity. A Christian's identity as a child of God can thus become the motivation force for moral behavior.